2021
DOI: 10.1007/s11356-021-16094-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of visible light active Mn-doped Bi2WO6-GO/MoS2 heterostructure for enhanced photocatalytic degradation of methylene blue

Abstract: The increase in environmental pollution has led to an increased investigation in the development of novel ternary photocatalytic systems for remediation. These Photocatalytic systems exhibit superior photocatalytic action for the removal of pollutants because of their visible light active bandgaps. A highly effective visible light active ternary heterojunction was fabricated using a hydrothermal method assisted by ultrasonication. Herein, we report the Insitu hydrothermal synthesis of Mn-doped Bi2WO6-GO/ MoS2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In I-FWGO, the stretching peaks of O-W-O and F-O-W shifted due to the iodine doping into the Fe-O lattice [24,25]. The peak intensity in the iodine-doped composite was lower than in the undoped counterpart and pristine FeWO 4 , confirming the successful insertion of dopant species in the host material [23]. FeWO4, with a bandgap of 2.0 eV, belongs to the wolframite family, which shows excellent photocatalytic activity due to various optical, electronic, and ferromagnetic properties [20].…”
Section: Ftir Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…In I-FWGO, the stretching peaks of O-W-O and F-O-W shifted due to the iodine doping into the Fe-O lattice [24,25]. The peak intensity in the iodine-doped composite was lower than in the undoped counterpart and pristine FeWO 4 , confirming the successful insertion of dopant species in the host material [23]. FeWO4, with a bandgap of 2.0 eV, belongs to the wolframite family, which shows excellent photocatalytic activity due to various optical, electronic, and ferromagnetic properties [20].…”
Section: Ftir Analysismentioning
confidence: 91%
“…The characteristic peaks of GO are shown around 1410 cm −1 , 1581 cm −1 , and 1711 cm −1 , which are attributed to COO − , C=C, and C=O stretching vibrations, respectively [22]. In both composites, two characteristic peaks correspond to W-O stretching and O-W-O stretching peaks at 832 cm −1 and 1034 cm −1 [23]. In I-FWGO, the stretching peaks of O-W-O and F-O-W shifted due to the iodine doping into the Fe-O lattice [24,25].…”
Section: Ftir Analysismentioning
confidence: 96%
“…117 According to 118 doping with Europium was the primary reason for the high activity of the photocatalyst, rather than changes in band gap absorption properties. Recently, Tahir and his team 119 reported on the in situ hydrothermal engineering of a Mn-doped Bi 2 WO 6 –GO/MoS 2 photocatalyst. They found that the Mn-doped composite had an absorption edge located in the visible zone with a gap energy of 2.2 eV.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…A modified version of Hummer’s technique was employed to produce graphene oxide (Fig. S1 ), as previously reported by our research group 42 . Prepared GO was dispersed ultrasonically and mixed in an aqueous solution containing boric acid in a 1:3 ratio, resulting in boron-doped graphene oxide synthesis 43 .…”
Section: Experimental and Synthesismentioning
confidence: 99%
“…More dye molecules adsorb to the catalyst surface as the dye concentration rises, thus, the active sites become saturated. Reduced light intensity at the catalyst surface results in less hydroxyl radical production, resulting in less efficient breakdown of methylene blue molecules 42 . A concentration of 15 ppm was found to be the optimum level for BGO-CuS, and 10 ppm was found to be optimum for GO-CuS and CuS.…”
Section: Effect Of Operational Parametersmentioning
confidence: 99%